English department students’ perceptions of utilizing social media for learning English - Alhaqi, Syifa Amalia Silmi; Hartati, Neti (LingTera, 2025)
This study investigates how English department students perceive the use of social media for learning English. A mixed-methods approach was employed, combining quantitative and qualitative data collected through questionnaires and structured interviews. A total of 88 students from several universities in Indonesia completed a 22-item questionnaire distributed via Google Forms, and three of these respondents were selected for follow-up interviews conducted via WhatsApp. Questionnaire responses were analyzed statistically, while interview data were examined using Miles and Huberman’s flow model. The findings indicate that students generally hold positive perceptions of using social media to support independent English learning. YouTube was identified as the most frequently used platform. Students reported that social media helps improve their comprehension, vocabulary development, and pronunciation, and described the experience as enjoyable and motivating beyond the classroom setting. Despite these benefits, students also encountered obstacles such as poor internet connectivity, concerns over data privacy, and exposure to inappropriate content.